URGENSI PENDIDIKAN PANCASILA TERHADAP PANDANGAN HIDUP HEDONISME MAHASISWA STKIP PGRI SUKABUMI - Karsini Karsini; Maulana Ibrohim Nugraha (Educatus, 2023)
Hedonism is a lifestyle that emphasizes the pursuit of pleasure and personal satisfaction without considering social norms, ethics, and moral values. This lifestyle has become increasingly prevalent in the era of globalization and digitalization, particularly among the younger generation in Indonesia. However, hedonism contradicts the values of Pancasila, which serves as the foundation of the Indonesian state and as a moral compass in national and societal life. Pancasila promotes a balance between rights and responsibilities, responsible freedom, and respect for humanity, justice, and morality. This study aims to determine the extent to which Pancasila Education influences the understanding and critical attitude of society—especially the youth—toward the hedonistic lifestyle. The research uses a qualitative method with data collected through literature studies from various scientific journals, questionnaires, and field observations. The results indicate that Pancasila Education plays an important role in instilling national values, ethics, and morals, thereby helping to suppress hedonistic tendencies in daily life. It also helps shape individuals into more thoughtful and responsible members of society in responding to the flow of global culture, encouraging a more balanced and accountable way of living. Therefore, Pancasila Education serves as a strategic instrument in building a generation with strong character and a national identity